Oral misoprostol for the prevention of primary post-partum hemorrhage during third stage of labor (2007)
Aim: To assess the effectiveness of oral misoprostol compared with methylergometrine in the prevention of primary post-partum hemorrhage during the third stage of labor. Methods: This was a randomized controlled trial of 864 singleton low-risk pregnant women. The outcomes were total blood loss, duration of the third stage of labor and peripartal change in hematocrit. Comparisons were by the c2-test and Student t-test. Relative risks were calculated for side-effects profile. A P-value of less than 0.05 was statistically significant. Results: The biodata of all the participants were similar. The mean blood loss for the misoprostol and methylergometrine groups was 191.6 _ 134.5 mL and 246.0 _ 175.5 mL, respectively (95% CI: -79.3 to -39.5 mL). The mean duration of the third stage of labor was 19.6 _ 2.4 min and 9.4 _ 3.3 min in the misoprostol and methylergometrine groups, respectively (95% CI: 9.82–10.58 min). More subjects had blood loss >500 mL, 42 (9.7%) versus 6 (1.4%), and peripartal hematocrit change greater than 10%, 38 (8.8%) versus 5 (1.2%), in the methylergometrine group than in the misoprostol group, respectively. Also, more subjects received additional oxytocic in the methylergometrine group, compared to the misoprostol group (80 [18.5%] versus 33 [7.6%] patients, respectively). Conclusions: Orally administered misoprostol was more effective in reducing blood loss during the third stage of labor than intramuscular methylergometrine. However, there were more subjects in the misoprostol group in whom duration of the third stage of labor was greater than 15 min and who also had manual placental removal than in the methylergometrine group